Effect of LPG Fuel Use on Engine Performance Yamaha Jupiter Z 2010: Effect of LPG Fuel Use on Engine Performance Yamaha Jupiter Z 2010 - Putra, Rian Ardiansyah Putra; harianto,; Abdul Kadir, (ReTII, 2022)
ABSTRACT LPG gas is included in the category of flammable gas that can be used as fuel in heating equipment and vehicles. This study aims to determine the effect and difference between motor performance from the use of pertalite, pertamax and LPG gas fuels on engine performance Yamaha Jupiter Z 2010. The tests carried out were testing torque, power, and then analyzing specific fuel consumption (SFC). Tests are carried out to calculate the ratio of torque, power and specific fuel consumption using pertalite, pertamax and LPG gas. The results showed the maximum torque on the use of pertalite fuel was 8.98 N.m at engine speed of 6108 rpm and maximum power on pertalite of 8.6 HP at 7587 . speed Rpm. Maximum torque with Pertamax fuel is 9.16 N.m at engine speed of 5159 rpm and maximum power on Pertamax is 8.8 HP at 8040 Rpm. While the maximum torque with Portable LPG fuel is 9.34 N.m at 5910 rpm and the maximum power of LPG gas is 9.0 HP at 7949 Rpm round. For specific fuel consumption using pertalite fuel The lowest is 0.0384 kg/HP-hour at 8000 rpm and the highest is 0.0832 kg/HP-hour at 8000 rpm. 4000 rpm. In Pertamax the lowest fuel is 0.0463 kg/HP-hour at 8000 rpm and highest at 1.0966 kg/HP-hour at 4000 rpm and the lowest on LPG gas is 0.3331 kg/HP-hour at 8000 rpm and the highest at 0.0666 kg/HP-hour at 4000 rpm. CO and HC exhaust emissions at a standard rotation of 4500 Rpm to 5500 Rpm from the three types of materials burn in stable condition. Keywords : LPG Gas, Torque, Power, Specific Fuel Consumption, Jupiter Z 2010